Veščina razreševanja interesnih konfliktov in elokventne artikulacije organizacijskega diskurza - Škerlep, Andrej (Teorija in praksa, 1998)
Article is defining public relations as skill of resolution of conflicts of interests between organization and its strategic stakeholders. In the process it refers to the theory of stakeholders management, to the elements of Gruning's theory of public relations and to the scheme of strategic negotiations as a matrix of relations between different interest positions. In the second part the article is concerned with brief overview of techniques of public relations which are defined as elements of organizational discourse,and of programs of public relations, in which it recognizes institutional contexts of organizational communication.
Keywords: odnosi z javnostmi; javnost; komuniciranje; communication; reševanje konfliktov